Analisis Kesadaran Pelaku UMKM Di Desa Kota Karang terhadap Pentingnya Legalitas Usaha - Imam Wahyudi; Paridatul Jannah; M.Rajesh Al Savero; Fathurrahman Imanullah; Sulys Setyorini; Muhammad Adi Satria (STKIP Subang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy. However, many MSMEs still lack formal business legality. This study aims to analyze the level of awareness of MSMEs regarding the importance of business legality and the factors that influence it. The research method used is a descriptive qualitative approach with data collection techniques through interviews and observations of MSMEs. The results indicate that MSME awareness of business legality is still low to moderate. The main factors influencing this low awareness include lack of knowledge, perceptions of the complexity of the licensing process, and minimal assistance from relevant parties. This study recommends increasing socialization and ongoing assistance to encourage the legalization of MSME businesses.